2013 AGU Named Lecturers and Section and Focus Group Awardees. (10th December 2013) - Williams, Danica
Abstract : Each year nearly 25 individuals are chosen to present lectures under the Bowie Lecture Series as well as the Section and Focus Group Named Lecture Series. The Bowie Lecture was inaugurated in 1989 to commemorate the 50th presentation of the William Bowie Medal, which is AGU's highest honor and is named for AGU's first president. Named lectures are designated by sections and focus groups to honor and memorialize distinguished scientists in their respective fields of science. This year's crop of lecturers represents some of the most innovative minds in their fields.